2017
DOI: 10.1590/0103-6440201701727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Material Shade and Distance from Light Curing Unit Tip on the Depth of Polymerization of Composites

Abstract: This study aimed to evaluate the effect of the composite shade and distance from the light-curing unit (LCU) tip on the irradiance reaching the bottom of composite disks and on the depth of polymerization. Composites of three shades (opaque -OXDC, bleach -BXL, and A2) were inserted into molds with 3-mm of thickness positioned over a spectrometer and photo-activated with the LCU (Bluephase) tip placed at 0 or 1 cm from the composite surface. The mean irradiance reaching the bottom of composite was recorded duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…It depends not only on the irradiance of the curing light and irradiation time but also on the distance of the light tip from the toothrestorative material. The light intensity diminishes as the tip of the source light moves away from the resin composite's surface 9,37 Because light disperses in open spaces, therefore, more evenly distributed light throughout the restoration is found at short distances between the tip of the LED-LCU&the surface of the restoration.While,longer curing distance causes light to disperse rather than focus on a certain area, thus decreasing the degree of polymerization 38 Thus,polymerization in depth can be expected to be hampered in more opaque materials where light transmission is jeopardized.DC depends on the emission spectra of LCU matching the absorption spectra of photo-initiators used in these materials&on the light actually reaching all portions of the restoration.Hence,reduction on conversion toward deeper areas was expected,with the more marked reduction being observed for the most opaque shade 23 The HV has been measured to evaluate the extent of polymerization,by comparing the hardness of the top surface to the bottom surface 8 This was in agreement with study 39 found significant differences in curing depth of pits and fissure sealants when the light source was placed directly upon the pit and fissure sealant in comparison to 5&10mm distances.Study 8 demonstrated that there was a significant difference in the Knoop hardness between 9 investigated distances(P < 0.001)in all LCU used in study.They conducted an inverse relationship exists between the lightcuring distance&the microhardness on the top&bottom of the composite.A Study 14 conducted the best results for DC % when there was maximum contact with a light source&exposure time was increased as long as it did not lead to adverse effects like increasing in tooth temperature.Study 40 did not measure light intensity but found that depth of cure was greatly affected by light source-specimen distance.It showed that although DOC did not follow Inverse Square law,but was reduced in linear manner with increasing light curingdistance.Study 41 conducted that Vickers hardness VHN values of all resin composites decreased with the increased irradiation distance.Study 42 confirmed a relation between the depth of cure at increasing distance to log10 of the mean light intensity.Their results showed that depth of cure decreased modestly and in a linear manner with increasing distance, however, intensity did not obey the inverse square law over distances 0-10 mm& the reduction in DOC at the extreme 15 mm separation distance was less than expected.Study 9 showed that regarding microhardness ratio,there were statistically significant differences for all analyzed factors; shade, distance and composite resin type,where there was decrease in values as the curing distance increased.The highest values were recorded at 0 mm& the lowest values at 12 mm.Study 37 analyzed the results of the LED at distances of 6&9 mm,found that there was decrease in DC at the 3&4mm thicknesses.They confirmed increase in curing distance promotes decrease in HV&DC for all LCUs studied.Study 38 concluded that curing distance&time both significantly affect the surface hardness of nano-filled composite resin.Light intensity is maximized if the curing distance is 0mm&the LCU is perpendicular to the composite surface, hence, polymerization of the composite resin is maximized.They found when the curing distance was longer than 5m...…”
Section: Microhardnesssupporting
confidence: 66%
“…It depends not only on the irradiance of the curing light and irradiation time but also on the distance of the light tip from the toothrestorative material. The light intensity diminishes as the tip of the source light moves away from the resin composite's surface 9,37 Because light disperses in open spaces, therefore, more evenly distributed light throughout the restoration is found at short distances between the tip of the LED-LCU&the surface of the restoration.While,longer curing distance causes light to disperse rather than focus on a certain area, thus decreasing the degree of polymerization 38 Thus,polymerization in depth can be expected to be hampered in more opaque materials where light transmission is jeopardized.DC depends on the emission spectra of LCU matching the absorption spectra of photo-initiators used in these materials&on the light actually reaching all portions of the restoration.Hence,reduction on conversion toward deeper areas was expected,with the more marked reduction being observed for the most opaque shade 23 The HV has been measured to evaluate the extent of polymerization,by comparing the hardness of the top surface to the bottom surface 8 This was in agreement with study 39 found significant differences in curing depth of pits and fissure sealants when the light source was placed directly upon the pit and fissure sealant in comparison to 5&10mm distances.Study 8 demonstrated that there was a significant difference in the Knoop hardness between 9 investigated distances(P < 0.001)in all LCU used in study.They conducted an inverse relationship exists between the lightcuring distance&the microhardness on the top&bottom of the composite.A Study 14 conducted the best results for DC % when there was maximum contact with a light source&exposure time was increased as long as it did not lead to adverse effects like increasing in tooth temperature.Study 40 did not measure light intensity but found that depth of cure was greatly affected by light source-specimen distance.It showed that although DOC did not follow Inverse Square law,but was reduced in linear manner with increasing light curingdistance.Study 41 conducted that Vickers hardness VHN values of all resin composites decreased with the increased irradiation distance.Study 42 confirmed a relation between the depth of cure at increasing distance to log10 of the mean light intensity.Their results showed that depth of cure decreased modestly and in a linear manner with increasing distance, however, intensity did not obey the inverse square law over distances 0-10 mm& the reduction in DOC at the extreme 15 mm separation distance was less than expected.Study 9 showed that regarding microhardness ratio,there were statistically significant differences for all analyzed factors; shade, distance and composite resin type,where there was decrease in values as the curing distance increased.The highest values were recorded at 0 mm& the lowest values at 12 mm.Study 37 analyzed the results of the LED at distances of 6&9 mm,found that there was decrease in DC at the 3&4mm thicknesses.They confirmed increase in curing distance promotes decrease in HV&DC for all LCUs studied.Study 38 concluded that curing distance&time both significantly affect the surface hardness of nano-filled composite resin.Light intensity is maximized if the curing distance is 0mm&the LCU is perpendicular to the composite surface, hence, polymerization of the composite resin is maximized.They found when the curing distance was longer than 5m...…”
Section: Microhardnesssupporting
confidence: 66%
“…The main possible reason for these results is the distance between the light source and the resin cement. Because the light curing distance affects the degree of conversion of resin cement [46], and the distance in C group is the lowest. The distance is a key factor that affects the conversion degree of resin cement [47], and a lower degree of conversion of resin cement might be correlated with an increased cytotoxicity [48].…”
Section: Discussionmentioning
confidence: 99%
“…SDR presents translucent universal color, while Z250 and NDU are of A2 shade. One may state that polymerization of resinous materials is correlated with light transmission and scattering 3,10,34. Namely, considering material’s translucency, the more translucent the composite, the more effective the composite’s polymerization 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…One may state that polymerization of resinous materials is correlated with light transmission and scattering 3,10,34. Namely, considering material’s translucency, the more translucent the composite, the more effective the composite’s polymerization 34,35. It should be highlighted, however, that not only the shade of composite interferes in translucency property but also its thickness, type, amount, and filler-size content, as well as refraction indices between fillers and matrix resin 35.…”
Section: Discussionmentioning
confidence: 99%